A qualitative analysis of experiencing a nature-related residential weekend workshop for women - O'Driscoll, Lucy M. (Northern Illinois University, 2000)
Includes bibliographical references (pages [85]-[89]) This thesis investigated women’s experience of a nature-related residential workshop using the methodology of phenomenology. Women are participating in naturerelated activities, but, due to limited research, it is unclear what those experiences may mean to them. Therefore, this study sought to discover and describe those experiences. The researcher designed and advertised a three-day nature-related workshop which incorporated several spiritual aspects of nature through indigenous teachings, rituals and ceremonies. Fifteen women from the general public attended the workshop; thirteen of those volunteered to participate in the research. These thirteen completed a written openended assessment of their experience and three women participated in formal interviews. Three interviews were completed within days of the workshop and a second interview was conducted four weeks later with the same three participants. This study found that each participant interviewed experienced varying degrees of 1) anxiety/fear, 2) connection, 3) insight/discovery, 4) positive feeling and 5) challenge. They described being at the workshop as a “once in a lifetime” opportunity and felt “blessed and privileged” to be there. Connections, insights and discoveries were made to nature, other women, ancestors, native culture, and the group. Some connections were spiritual and so deep they “touched some core within.” Participants felt “empowered and strengthened” by their accomplishments, and felt good when they a) took leadership roles, b) felt prepared with proper attire, c) helped others, d) received kindness shown to them, ABSTRACT i e) worked together as a group, f) identified with others, g) shared stories and laughter, and h) participated in ceremonies and rituals. They also felt good that it was a women’s group. The workshop components which were successful for this group included: a) the f challenging hike to the remote lodge, b) spending time in a wilderness setting, c) allowing plenty of unstructured time, d) participating in ceremonies and rituals, e) building community through cooperative activities and sharing circles, f) sharing good meals, and g) experiencing the respectful leadership style. These findings provide useful insights and may assist professionals either designing or delivering nature-related workshops for women. This study helps to understand how women experience a nature-related workshop. M.S. Ed. (Master of Education)